2017
DOI: 10.3988/jcn.2017.13.2.121
|View full text |Cite
|
Sign up to set email alerts
|

CT Angiography of Collateral Vessels and Outcomes in Endovascular-Treated Acute Ischemic Stroke Patients

Abstract: Background and PurposeMeasuring the extent of the collateral blood vessels using computed tomography (CT) angiography source images may promote tissue survival and functional gain in acute ischemic stroke patients who are candidates for endovascular recanalization treatment.MethodsOf 5,558 acute stroke patients registered in a prospective clinical stroke registry, 104 met the selection criteria of endovascular recanalization treatment for internal cerebral artery or middle cerebral artery main-stem (M1) occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The good collateral was the only significant factor in good outcome at 3 months. The sufficient baseline collateral status in acute ischemic stroke patients was associated with improved functional recovery and decreased mortality rate at 3 months after stroke (15). Our study showed similar results that collaterals are important for the clinical outcome of acute ischemic stroke patients.…”
Section: Discussionsupporting
confidence: 76%
“…The good collateral was the only significant factor in good outcome at 3 months. The sufficient baseline collateral status in acute ischemic stroke patients was associated with improved functional recovery and decreased mortality rate at 3 months after stroke (15). Our study showed similar results that collaterals are important for the clinical outcome of acute ischemic stroke patients.…”
Section: Discussionsupporting
confidence: 76%
“…However, there has been no consensual grading system established to evaluate leptomeningeal collaterals on CTA. To avoid arbitrary grading, we tried to choose collateral assessment methods that have all been widely used in previous studies [ 21 , 22 ]. Based on the consistent findings from those collateral assessment methods, we regrouped the leptomeningeal collaterals by its cutoff value into incomplete or complete.…”
Section: Discussionmentioning
confidence: 99%
“…Collateral status is a commonly used method that reflects hypoperfusion severity. Robust collateral flow is associated with smaller ischemic core lesions and slower progression, which may lead to improved clinical outcomes [ 1 , 2 , 3 , 4 ]. Moreover, time windows for EVT eligibility can be determined based on the collateral status.…”
Section: Introductionmentioning
confidence: 99%